Students' readiness in following online learning during the Covid-19 pandemic - Siti Wakijah; Thomas Sukardi; Putu Sudira; Pramu Pramu; Ranu Iskandar; Rijalul Haq (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
The Covid-19 pandemic has impacted various sectors, including the education sector. This study aimed to determine Polbangtan YoMa students' readiness to follow online learning during the Covid-19 pandemic. This research is survey research. The subjects of this study were 158 Polbangtan YoMa students. The instrument used for data collection was a questionnaire. Data were analyzed using descriptive statistics. This study results are: (1) the aspects of facilities and infrastructure get the percentage of 66%, meaning that Polbangtan YoMa students are ready to follow the learning from the aspect of facilities and infrastructure; (2) the technological literacy aspect gets the percentage of 65%; meaning the Polbangtan YoMa students are ready to follow the learning from the aspect of their technological literacy abilities; (3) the quality aspect of online interactions gets the percentage 35%; meaning that Polbangtan YoMa students are not ready to take part in learning from the aspect of online interaction quality capabilities; (4) aspects of the benefits of online learning get the average sroce percentage of 52%, meaning that Polbangtan YoMa students agree that online learning will be helpful; (5) aspects of assistance services get the percentage of 67%, meaning that Polbangtan YoMa students entirely agree that assistance services help in online learning; and (6) aspects of online learning prospects get the average score percentage of 57%, meaning that Polbangtan YoMa students somewhat agree that online learning provides online learning prospects, thus Polbangtan YoMa students are ready to do online learning with an average proportion of 57%. The online learning model used at Polbangtan YoMa is asynchronous learning using e-learning, WhatsApp, and Google Classroom.